Pengembangan Pendidikan Kewarganegaraan Demokratis di Amerika Serikat - Hidayah, Eva Nur; Rinenggo, Alil (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2022)
Citizenship education provided by each country aims to guide and shape the character of good citizens and create democratic citizens. The United States of America is a country that initiates citizenship education lessons and is one of the superpowers in the world because of its economic and political strength. The method used in writing this article uses the literature review method with the main data source, namely library data, consisting of books, journals, and internet sites related to the topic. The data analysis technique used in this article is content analysis. The discussion of this article is focused on the national policy and content of the civic education curriculum in the United States which can be assessed as civic education leading closer to the continuum of maximal civic education.Keywords: citizenship education, democratic, United States of America.